A framework for the systematic realisation of phenomena for enhanced sensing of radiological and nuclear materials, and radiation - Healy, Matthew J. F. (IOP Publishing, 2015)
The quest for new sensing phenomena continues because detecting, discriminating, identifying, measuring and monitoring nuclear materials and their radiation from greater range, at lower concentrations, and in a more timely fashion brings greater safety, security and efficiency. The potential phenomena are diverse, and those that have been realised can be found in disparate fields of science, engineering and medicine, which makes the full range difficult to realise and record. The framework presented here offers a means to systematically and comprehensively explore nuclear sensing phenomena. The approach is based on the fundamental concepts of matter and energy, where the sequence starts with the original nuclear material and its emissions, and progressively considers signatures arising from secondary effects and the emissions from associated materials and the environment. Concepts of operations such as active and passive interrogation, and networked sensing are considered. In this operational light, unpacking nuclear signatures forces a fresh look at the sensing concept. It also exposes how some phenomena that exist in established technology may be considered novel based on how they could be exploited rather than what they fundamentally are. This article selects phenomena purely to illustrate the framework and how it can be best used to foster creativity in the quest for novel phenomena rather than exhaustively listing, categorising or comparing any practical aspects of candidate phenomena.